1966
DOI: 10.1136/bmj.1.5489.714
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Studies of Small Bowel in Ankylostomiasis

Abstract: Non-specific Haemorrhagic Proctocolitis-Riis et al. MEDICALJOURThe main reason for discrepancy between the two methods of evaluation thus seems to be a difference of threshold. SummarySixty-five episodes of complete clinical remission in 46 patients with a verified diagnosis of non-specific haemorrhagic proctocolitis were studied with respect to macroscopic and microscopical signs of mucosal inflammation.The microscopical evaluation was based on the cytological method described in a previous paper. Macroscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1

Year Published

1968
1968
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 7 publications
(7 reference statements)
1
8
1
Order By: Relevance
“…Also, similar morphological changes of the intestinal mucosa have been described in a variety of clinical situations, including overt tropical sprue (Butterworth and Perez-Santiago, 1958;Chacko et al, 1961;Baker et al, 1962;Falaiye, 1970), kwashiorkor (Burman, 1965;Stanfield et al, 1965), hookworm disease in India (Tandon et al, 1966), and rosacea (Watson et al, 1965). It is clear therefore that these histological changes do not have any diagnostic significance when taken alone.…”
Section: Occurrence Of Intestinal Abnormalitiesmentioning
confidence: 62%
See 1 more Smart Citation
“…Also, similar morphological changes of the intestinal mucosa have been described in a variety of clinical situations, including overt tropical sprue (Butterworth and Perez-Santiago, 1958;Chacko et al, 1961;Baker et al, 1962;Falaiye, 1970), kwashiorkor (Burman, 1965;Stanfield et al, 1965), hookworm disease in India (Tandon et al, 1966), and rosacea (Watson et al, 1965). It is clear therefore that these histological changes do not have any diagnostic significance when taken alone.…”
Section: Occurrence Of Intestinal Abnormalitiesmentioning
confidence: 62%
“…Parasitic Infestations.-It has been recognized that certain parasitic infestations of the gastrointestinal tract, particularly with heavy loads of Strongyloides stercoralis (Milner et al, 1965), Ciardia lamblia (Amini, 1963), and hookworm disease in India (Tandon et al, 1966(Tandon et al, , 1969, may disrupt mucosal structure and function in the small bowel. In the two studies frcm Africa relating to hookworm disease and intestinal absorptive capacity Gilles et al (1964) and Banwell et al (1967) could not find any association between infestation with this parasite and intestinal malabsorption.…”
Section: Aetiological Considerationsmentioning
confidence: 99%
“…85,86 It has been suggested that the neutralization of digestive proteases by hookworm-derived, broad-spectrum protease inhibitors, although protecting the parasite from the proteolytic environment of the small intestine, contributes to malnourishment and impairment of physical growth by interfering with the intestinal absorption of nutrients. 87 In support of this theory, hamsters immunized with AceKI-1 and then challenged with A ceylanicum hookworms were partially protected against hookworm-associated growth delay without a measureable effect on anemia, suggesting that the prevention of growth delay is due to downstream effects of antibody-mediated neutralization of protease inhibitors and not directly related to parasite death.…”
Section: Molecular Mechanisms Associated With Host Defense and Immunementioning
confidence: 99%
“…While the anemia is presumably due to the cumulative effect of chronic intestinal blood loss, the molecular mechanisms underlying the pathogenesis of hookworm malnutrition remain unknown. Although it has been suggested that hookworm malnutrition and growth delay occur secondary to chronic iron deficiency, particularly in children, evidence from prior clinical studies suggests that hookworm infection is also associated with various degrees of intestinal malabsorption (18,35,54,57,62). It has been hypothesized that this hookworm malabsorption syndrome might occur secondary to mucosal inflammation triggered by the adult worm attached to the intestinal epithelium or might be a result of secretion of parasite inhibitors of host digestive enzymes (18).…”
mentioning
confidence: 99%